Tabela de Derivadas
FUNÇÃO
DERIVADA DA FUNÇÃO
01) y = c y' = 0 
02) y = x  y' = 1
03) y = cu  y' = cu'
04) y = u + v  y' = u' + v'
05) y = uv y' = u'v + uv' 
06)
07) y = un y' = n.un - 1.u'
08) y = au (a > 0, )
09) y = eu y' = eu. u' 
10) y = y' =
11) y = uv (u > 0) 
12) y = ln u
13) y = sen u y' = cos u.u' 
14) y = cos u y' = - sen u.u' 
15) y = tg u y' = sec2u.u' 
16) y = sec u y' = sec u . tg u . u' 
17) y = cotg u  y' = - cosec2u.u'
18) y = cosec u  y' = - cosec u . cotg u . u'
19) y = arc sen u 
20) y = arc cos u 
21) y = arc tg u 
22) y = arc cotg u
23) y = arc cosec u,  , |u| > 1 
24) y = arc sec u,  , |u| > 1 
25) y = senh u y' = (cosh u).u' 
26) y = cosh u y' = (senh u).u' 
27) y = tgh u y' = (sech2 u).u' 
28) y = cotgh u y' = (-cosech2 u).u' 
29) y = sech u y' = (-sech u).(tgh u).u' 
30) y = cosech u y' = (-cosech u).(cotgh u).u' 
31) y = arg senh u
32) y = arg cosh u , u > 1 
33) y = arg tgh u , |u| < 1 
34) y = arg cotgh u , |u| > 1 
35) y = arg sech u , 0 < u < 1 
36) y = arg cosech u ,
37) y = f(g(x)) y' = f ' (g(x)). g'(x)
38) y = loga |u|
 
 
u, v = funcões
n, a = ctes
arc sen u = sen-1 
arc cotg u = cotg-1
arc cos u = cos-1 
arc cosec u = cosec-1 
arc tg u = tg-1 
arc sec u = sec-1